Ability self-concepts and parental support may protect adolescents when they experience low support from their math teachers. (April 2021) - Lee, Glona; Simpkins, Sandra D.
Abstract: Introduction: Experiencing low support from teachers can be associated with low academic achievement. Nonetheless, individual- (i.e., ability self-concepts) and contextual-level (i.e., parental support) protective factors may help adolescents to display academic resilience. This study examined whether high school students' math ability self-concepts and parental support can mitigate the possible negative association between perceived low math teacher support and their math achievement. Method: Correlational data were drawn from the High School Longitudinal Study ( N = 14, 580, M age = 17.42 in 11 th grade, 51% female), a nationally representative study of high school students in the U.S. The measures of protective factors (i.e., math ability self-concepts and parental support) were obtained from the surveys administered to students and parents in 9 th grade. Students' perceived teacher support and their math achievement score were measured in 11 th grade. A series of linear regression analyses were estimated to test our hypotheses. Results & Conclusions: Perceived low teacher support was negatively associated with adolescents' math achievement. Adolescents' math ability self-concepts were directly and positively associated with their math achievement. The interaction between perceived low teacher support and ability self-concepts in predicting adolescents' achievement varied by parental support. The association between perceived low teacher support and adolescents' math achievement was not statistically significant when adolescents were high on one of the protective factors. That is, high parental support may be protective for adolescents with low math ability self-concepts. This study highlights the interaction between adolescents' academic motivation and parental support in demonstrating resilience to perceived low teacher support.